The effect of interview structure in interview transcript on applicants' reactions : a laboratory experiment - Mohd. Taib, Maisarah; Alias, Alizi (2008)
The present study has examined the effects of interview structure on applicants’ reactions by comparing among structured, semi-structured and unstructured interview. Forty-one final year undergraduate psychology students participated in the present study and they were asked to imagine themselves as applicants for the post of research assistant (RA) and they were interviewed via interview transcripts. Prior to answering the interview questions in the transcript, they were asked to read a job description of RA. Afterward, counterbalanced interview transcripts were distributed to all of them. Once everyone finished, participants responded to applicants’ reactions self-report survey. The results showed a significant effect of interview structure on applicants’ reactions with F (1, 40) =35.289; p<0.01. Particularly, applicants reacted negatively to structured interview compared to semi-structured (t (41) =-8.67; p<0.01) and unstructured interview (t (41) = -5.94; p<0.01). No significant difference was found in applicants’ reactions between semi-structured and unstructured interview with t (41) = 1.56; p>0.05. The findings were then discussed in relation to review of past literature, in addition to the study’s limitations and its implications were discussed with further suggestions for future research.